PENERAPAN MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) BERBANTUAN MEDIA KLIPING UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN - Syifa Alyadani, - (2022)
Latarbelakang yang menjadikan pelaksanaan penelitian ini ialah kondisi kemampuan membaca pemahaman siswa kelas IV SDN Karang Tengah yang rendah. Hal tersebut karena mayoritas siswa tidak mencapai kriteria ketuntasan minimal (KKM) yakni ≥ 70. Dengan diterapkannya model pembelajaran Cooperative Integrated reading and composition (CIRC) berbantuan media kliping dapat dijadikan solusi guna memperbaiki permasalahan tersebut. Model pembelajaran CIRC berbantuan media kliping bisa menjadi solusi untuk meningkatkan kemampuan membaca pemahaman dan siswa dapat terlatih untuk kreatif dan bersosialiasi melalui kegiatan bekerja sama. Desain penelitian ini yaitu penelitian tindakan kelas desain Kemmis dan Mc. Taggart yang terdiri dari tahap planning, acting, observing, dan reflecting. Pengumpulan data menggunakan observasi, tes esai, dan dokumentsi. Instrumen yang diperlukan menggunakan tes esai dan observasi. Kemudian data yang didapatkan akan diolah menggunakan analisis data kuantitatif hasil nilai evaluasi serta data kualitatif hasil observasi. Perolehan penelitian menunjukkan peningkatan pada kemampuan membaca pemahaman siswa dengan perolehan rata-rata siklus I (68,5%) dan siklus II (91,4%). ----- This research is based on the poor condition of fourth grade students' reading comprehension ability at SDN Karang Tengah, especially in the subject of Bahasa Indonesia semester II where the minimum criteria of mastery learning (KKM) is ≥ 70. The learning model Cooperative Integrated Reading and Composition (CIRC) assisted by clipping media may be the solution to improve the poor condition of fourth grade students' reading comprehension ability at SDN Karang Tengah because this method may improve the students' reading comprehension ability to comprehend texts and the students' creativity in writing and reproducing based on what they have read. The learning model Cooperative Integrated Reading and Composition (CIRC) assisted by clipping media may also create a different and fun learning atmosphere because the students are trained to be creative and cooperative in working together with their heterogeneous group, in which may also improve the students' ability to socialize with their classmates. This research was conducted by using Classroom Action Research (PTK) method by Kemmis and Taggart in two cycles which consists of planning, implementation, observation, and reflection. The data collection was conducted by using observation, essay tests, and documentation. This research was conducted by applying essay tests and observation as the research instruments to observe the improvement of the students' reading comprehension ability. The data that had been collected then would be processed by using quantitative data analysis as the result of the evaluation of reading comprehension ability, and qualitative data as the result of observation. The result of this research shows the improvement of the students' reading comprehension ability in the activities and the results of learning with the average of 68,5% in cycle I to the average of 91,4% in cycle II.